PENGARUH ROLE STRESSOR DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KEPUASAN KERJA PEGAWAI - Srimulyani, Veronika Agustini (Widya Warta, 2010)
Basically, the problem of work stress is often referred to the notion of stress at working environment, which involves interaction processes between an employee and his work aspects. The most significant source of stress is role stressor. Role stressor comprises role ambiguity, role conflict, and role overload. Role stressor and perceived organizational support (POS) are the antecedents of job satisfaction or job dissatisfaction. The subject of the research was the employees of LPKBM Madcoms Madiun. The result of the multiple regression analysis showed: (a) role ambiguity had a negative effect on job satisfaction, but it was not significant, (b) role conflict and role overload had a negative effect on job satisfaction, and it was significant, and (c) perceived organizational support had a positive effect on job satisfaction, and it was significant.